(untitled) (Carte Romanze, 2020)
This contribution reflects on the tripartite conception of love that Boccaccio draws from Aristotle’s VIII book of Ethica Nicomacheaand the related Commentary by Thomas Aquinas, preserved in the ms. Ambrosiano A 204 inf. The hierarchy between honest, delightful and useful love is maintained in many of Boccaccio’s works, and acquires a greater complexity in some love novels of the Decameron. The tripartition assimilated by the Aristotelian Ethica is applied in particular to the long talk of Ghismonda in Dec. IV 1.